Repurposing Cefazolin-Avibactam for the Treatment of Drug Resistant Mycobacterium tuberculosis - Srivastava, Shashikant; Gumbo, Tawanda; Thomas, Tania (Frontiers in Pharmacology, 2021)
Background. While tuberculosis (TB) is curable and preventable, the most effective first-line antibiotics cannot kill multi-drug resistant (MDR) Mycobacterium tuberculosis (Mtb). Therefore, effective drugs are needed to combat MDR-TB, especially in children. Our objective was to repurpose cefazolin for MDR-TB treatment in children using principles of pharmacokinetic/pharmacodynamics (PK/PD). Methods. Cefazolin minimum inhibitory concentration (MIC) was identified in 17 clinical Mtb strains, with and without combination of the -lactamase inhibitor, avibactam. Next, dose-ranging studies were performed using the intracellular hollow fiber model of TB (HFS-TB) to identify the optimal cefazolin exposure. Monte Carlo experiments were then performed in 10,000 children for optimal dose identification based on cumulative fraction of response (CFR) and Mtb susceptibility breakpoint in three age-groups. Results. Avibactam reduced the cefazolin MICs by five tube dilutions. Cefazolin-avibactam demonstrated maximal kill of 4.85 log10 CFU/mL in the intracellular HFS-TB over 28 days. The % time above MIC associated with maximal effect (EC80) was 46.76% (95% confidence interval: 43.04-50.49%) of dosing interval. For 100 mg/kg once or twice daily, the CFR was 8.46% and 61.39% in children <3 years with disseminated TB, 9.70% and 84.07% for 3-5 years-old children, and 17.20% and 76.13% for 12-15 years-old children. The PK/PD-derived susceptibility breakpoint was dose dependent at 1-2 mg/L. Conclusion. Cefazolin-avibactam combination demonstrates efficacy against both drug susceptible and MDR-TB clinical strains in the HFS-TB and could potentially be used to treat children with tuberculosis. Clinical studies are warranted to validate our findings.